A review of the interaction between the striker and the goalkeeper at the individual tactical level in football - Peterson, S. W.; Bruton, M. R. (International Journal of Sports Science & Coaching, 2020)
Recent performance analysis techniques have attempted to move beyond a narrow focus on game outcomes by considering the game, team, group and individual tactical levels. Goals are decisive in football, yet the extent to which the individual goalkeeper had been studied was unknown. We therefore systematically searched the literature to determine the extent of studies that included actions related to the goalkeeper; of 711 titles retrieved, six met the full inclusion criteria. Despite sound study design in general, the use of World Cup matches might limit the generalisability of findings. Only 21% of the outcome variables extracted were comparable across studies, with 58 different variables used to describe actions involving the goalkeeper, which suggested significant conceptual disparity. Of greater concern, no studies presented the striker and goalkeeper interaction in relative terms. The development of an analytic model that quantifies this relationship is necessary to adequately characterise tactics and inform the practical requirements of goalkeeping tactical training.